Comparison of 68Ga-FAPI and 18F-FDG PET/CT for the diagnosis of primary and metastatic lesions in abdominal and pelvic malignancies: A systematic review and meta-analysis - Liu, Xue; Liu, Huiting; Gao, Cailiang; Zeng, Wenbing (Frontiers in Oncology, 2023)
Purpose: The purpose of this study is to compare the application value of 68Ga-FAPI and 18F-FDG PET/CT in primary and metastatic lesions of abdominal and pelvic malignancies (APMs). Materials: The search, limited to the earliest available date of indexing through 31 July 2022, was performed on PubMed, Embase, and Cochrane Library databases using a data-specific Boolean logic search strategy. We calculated the detection rate (DR) of 68Ga-FAPI and 18F-FDG PET/CT in the primary staging and recurrence of APMs, and pooled sensitivities/specificities based on lymph nodes or distant metastases. Results: We analyzed 473 patients and 2775 lesions in the 13 studies. The DRs of 68Ga-FAPI and 18F-FDG PET/CT in evaluating the primary staging and recurrence of APMs were 0.98 (95% CI: 0.95-1.00), 0.76 (95% CI: 0.63-0.87), and 0.91(95% CI: 0.61-1.00), 0.56 (95% CI: 0.44-0.68), respectively. The DRs of 68Ga-FAPI and 18F-FDG PET/CT in primary gastric cancer and liver cancer were 0.99 (95% CI: 0.96-1.00), 0.97 (95% CI: 0.89-1.00) and 0.82 (95% CI: 0.59-0.97), 0.80 (95% CI: 0.52-0.98), respectively. The pooled sensitivities of 68Ga-FAPI and 18F-FDG PET/CT in lymph nodes or distant metastases were 0.717(95% CI: 0.698-0.735) and 0.525(95% CI: 0.505-0.546), and the pooled specificities were 0.891 (95% CI: 0.858-0.918) and 0.821(95% CI: 0.786-0.853), respectively. Conclusions: This meta-analysis concluded that 68Ga-FAPI and 18F-FDG PET/CT had a high overall diagnostic performance in detecting the primary staging and lymph nodes or distant metastases of APMs, but the detection ability of 68Ga-FAPI was significantly higher than that of 18F-FDG. However, the ability of 68Ga-FAPI to diagnose lymph node metastasis is not very satisfactory, and is significantly lower than that of distant metastasis.